Egypt at its origins 2 : proceedings of the international conference "Origin of the State, Predynastic and Early Dynastic Egypt", Toulouse (France), 5th-8th September 2005 - Midant-Reynes, Béatrix; Tristant, Yann; Rowland, J.; Hendrickx, Stan (Orientalia Lovaniensia analecta, 2008)
"The proceedings of the Second International Conference about Predynastic and Early Dynastic Egypt (Toulouse, France, 2005) present the results of the latest research on the rise of the Pharaonic culture in Ancient Egypt. It contains 65 contributions by 80 authors from different countries. The articles in this volume have been organised in nine thematic sections: craft and craft specialisation; physical anthropology; geoarchaeology and environmental sciences; interactions between Upper and Lower Egypt; interactions between the desert and the Nile Valley; foreign relations; birth of writing and kingship; cult, ideology and social complexity; excavations and museums."--BOOK JACKET.